Nanostructures assembly and the property of polysaccharide extracted from Tremella Fuciformis fruiting body - Wang, Deqiang; Wang, Deguo; Yan, Tingxuan; Jiang, Weifeng; Han, Xinya; Yan, Jvfen; Guo, Yanrong (International journal of biological macromolecules, 2019)
Polysaccharides from fungi are good free radical scavengers. However, there are no enzymes digesting these polysaccharides in the human body, which limits the use of fungal polysaccharides. Therefore, it is of great significance to study the preparation methods of fungal polysaccharides to improve the utilization rate of fungal polysaccharides. In this paper, the acidic polysaccharide of Tremella fuciformis was extracted by boiling and precipitated by ethanol. The total sugar content obtained by freeze-drying after ion exchange chromatography purification was 93.6%. It is mainly composed of mannose, glucuronic acid, xylose and fucose. According to the peak area, the mass ratio of the substance is about 6.8:1:1.5:0.6, which indicates that TFP is a polysaccharide with mannose as its main chain and glucuronic acid, fucose and xylose as well as a small amount of glucose as the branch chain. Molecular weight is 1.86 × 106 Da. The existence of glucuronic acid endows polysaccharides with negative charge in aqueous solution and can be assembled into nanostructures with chitosan. By measuring the swelling property in aqueous, it shows the TFP separated from Tremella fuciformis fruits is suitable for drug controlled release. •The polysaccharide extracted from Tremella Fuciformis Fruiting body, and characterized by HPLC, FTIR, HPGPC, 1H NMR/13C NMR.•Methods of nanostructures assembly of Tremella Fuciformis polysaccharide with chitosan were reported.•The nanostructures were characterized by FTIR, SEM and DLS.•The properties of medicine encapsulation and heavy metal ions absorption of the nanostructures were investigated